Screening of Prophage Sequences Among Helicobacter Pylori - Timóteo, Andreia (2013)
Until recently, Helicobacter pylori was considered a bacterium without prophages. The presence of an incomplete prophage sequence in strain B38 and a complete prophage sequence in strain B45 showed otherwise. Using a PCR strategy, based on degenerated primers designed after aligning bacteriophage integrase genes from H. pylori strains B38 and B45, and H. acinonychis prophage II, we found that integrase sequence was present in 21.4% (73/341) of the H. pylori clinical strains tested. The phylogenetic analysis of the sequenced region revealed that strains cluster according to their geographic origin, but not to their pathology. We have applied the same methodology to additional 147 European strains and 77 African strains, determining the presence of integrase sequence in 25.2% (37/147) of the former and in 19.5% (15/77) of the latter. Currently, we have a total of 565 strains screened for the presence of integrase gene, with 125 positive for this sequence (22.1%). To understand if these integrase sequences belong to reminiscent or complete prophages we are also screening for the presence of other prophage coding sequences. Among integrase positive strains, we found 19.2% (5/26) positive strains for the primase sequence and 53.3% (8/15) for the presence of the end of the phage. Presently, we are running the sequencing of the PCR amplified products in order to conduct the phylogenetic analysis. The results reinforce the abundance of prophages sequences in H. pylori and suggest that the majority of them belong to reminiscent prophages integrated within the bacterium genome.